2004
DOI: 10.1128/jb.186.24.8524-8528.2004
|View full text |Cite
|
Sign up to set email alerts
|

The F-ATPase Operon Promoter of Streptococcus mutans Is Transcriptionally Regulated in Response to External pH

Abstract: Streptococcus mutans F-ATPase, the major component of the acid-adaptive response of the organism, is transcriptionally upregulated at low pH. Fusions of the F-ATPase promoter to chloramphenicol acetyltransferase indicated that pH-dependent expression is still observed with a short promoter that contains a domain conserved between streptococcal ATPase operons.During growth at acidic pH values, Streptococcus mutans and S. sanguis both increase production of their F-ATPases (4,5,12). By pumping protons out of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 30 publications
5
76
0
Order By: Relevance
“…F-type ATPases that use an electrochemical gradient of H + or Na + to synthesize ATP, or hydrolyse ATP to reverse an electrochemical gradient, are known to play important roles in maintaining internal pH (pH i ) homeostasis (Cotter & Hill, 2003;Quivey et al, 2001). For example, the protontranslocation F 1 F 0 -H/ATPase operon in S. mutans consists of eight genes, atpEBF and atpHAGDC, which respectively encode the c, a and b subunits of the membrane-embedded F 0 complex and the d, a, c, b, and e subunits of the peripherally bound F 1 protein (Kuhnert et al, 2004). The F 0 complex has proton-translocating activity, while the F 1 complex has ATPase activity.…”
Section: Upregulated Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…F-type ATPases that use an electrochemical gradient of H + or Na + to synthesize ATP, or hydrolyse ATP to reverse an electrochemical gradient, are known to play important roles in maintaining internal pH (pH i ) homeostasis (Cotter & Hill, 2003;Quivey et al, 2001). For example, the protontranslocation F 1 F 0 -H/ATPase operon in S. mutans consists of eight genes, atpEBF and atpHAGDC, which respectively encode the c, a and b subunits of the membrane-embedded F 0 complex and the d, a, c, b, and e subunits of the peripherally bound F 1 protein (Kuhnert et al, 2004). The F 0 complex has proton-translocating activity, while the F 1 complex has ATPase activity.…”
Section: Upregulated Genesmentioning
confidence: 99%
“…Previous studies suggested that the F 1 F 0 -ATPase in S. mutans might be constitutively expressed, since the promoter analysis of the F 1 F 0 -ATPase operon showed a putative Pribnow box (TAAACT) and a clear 235 sequence of TTGACA, homologous with the canonical s 70 promoter in E. coli, suggesting a housekeeping function for F 1 F 0 -ATPase synthesis (Quivey et al, 2001). However, using transcriptional reporter gene fusions to the promoter of the atp operon, Quivey and colleagues found that the increase in F 1 F 0 -H/ATPase activity was correlated with increased transcription of the atp operon of S. mutans grown at low pH (Kuhnert et al, 2004 (Kakinuma, 1998;Magalhaes et al, 2005). For instance, the copYAZ operon in S. mutans encodes a Ptype ATPase responsible for transport of copper, allowing this organism to tolerate the high concentrations of copper potentially released from dental amalgam (Vats & Lee, 2001).…”
Section: Upregulated Genesmentioning
confidence: 99%
“…The organism is able to persist in the oral cavity by adapting to environmental stresses, particularly the acidification of its milieu (18,30). It has been established that the F-ATPase is transcriptionally up-regulated during growth at pH values below 7 (16,17). Recently, we have shown that the membrane fatty acid composition of S. mutans changes dramatically during growth at low pH values (7,8,28).…”
Section: Discussionmentioning
confidence: 99%
“…RNA was extracted from overnight batch cultures of S. mutans UA159 with a QIAGEN RNeasy mini kit with modifications, as previously described (17). The Promega (Madison, Wis.) avian myeloblastosis virus reverse transcriptase primer extension system was used to label an oligonucleotide primer, SmnPE3 (Table 2), with [␥-32 P]ATP (6,000 Ci/mmol) (Perkin Elmer, Boston, Mass.).…”
mentioning
confidence: 99%
“…The internal acidification also reduces the activity of acidlabile enzymes and damages proteins and DNA (van de Guchte et al, 2002). To stabilize the transmembrane pH during an acidic challenge, the multimeric F 0 F 1 -ATPase is utilized to expel protons out of the cell (Kuhnert et al, 2004;Suzuki et al, 2000). Mutations in the b (AtpD) and c (UncG) subunits of the F 0 F 1 -ATPase resulted in mutacin I defective phenotypes.…”
Section: Stress-response Genesmentioning
confidence: 99%